Marcas corporais, marcas sociais : experiência de mulheres com reações hansênicas - Silva, Lidiane Mara de Ávila e (2014)
Leprosy is currently constitutes as a public health problem and despite significant reduction, Brazil ranks second in the world in number of cases. This scenario highlights the state of Mato Grosso, whose magnitude indicates how much it is still a challenge to be faced by the field of Public Health. Although the detection and treatment are provided in primary care, a percentage of diseased may develop leprosy reactions that constitute as a grievance to leprosy producing body marks such as spots, desquamation and ulceration of the skin, subcutaneous nodules, among other changes refer to the sphere of meanings and affect the identity of these people by giving visibility to a condition that can lead them to be socially stigmatized. This study examines the experience of women with leprosy reactions, interpreted by practical common sense knowledge from the perspective of the interviewees. It is a qualitative research, which draws on the studies of the experience of a neglected tropical disease with potentially stigmatizing, based on assumptions of phenomenology. The results were analyzed in categories covering: the process of discovery of the disease, in which we highlight the late diagnosis and the lack of preparation of professionals and staff at the primary health care; notions of causality, leprosy is attributed to dirty places and the microorganisms that invade the body; the concept of leprosy and leprosy reactions, related to a disease that affects the nerves and their sequelae, respectively; impacts and daily confrontations, especially pain, which assumes a central aspect in this experiment; social support received especially the children, religious institutions and health professionals; the relationship to treatment and future expectations, focusing on getting back to normal life. These categories elucidate the complexity of aspects that influence the illness experience by leprosy reactions, showing that brands directly affect the social life of fallen ill, causing them to isolate themselves socially. We emphasize that the proposition more sensitive to sociocultural specific interventions can make attention to more humane and comprehensive sickened.